Differential diagnosis and therapeutic conduct for periapical bone dysplasia: case report (Research, Society and Development, 2020)
Periapical bone cement dysplasia has been desc Periapical bone cement dysplasia has been described as a condition that generally affects the maxilla and mandible bones, occurring mainly in black or Asian women in a middle age group. It is a lesion of unknown etiology whose diagnosis, which is carried out by means of routine dental exams, is extremely important so that undue treatments are not carried out. The objective of this study is to carry out a differential diagnosis related to dysplasic lesion and endodontic periapical lesion. , as a therapeutic approach, to report a clinical case of a 38-year-old female patient who presented to the Polyclinic of Faculdade Patos de Minas for routine dental treatment. After radiographic examination, a radiolucent area was detected, which, after a positive vitality test, was diagnosed as periapical bone cement dysplasia. Weekly laser therapy associated with 1% methylene blue will be used to attempt to regress the dysplastic lesion and improve the periodontal condition, in order to remedy the present purulent collection. The treatment of the lesion when it is decided not to enter surgical methods is palliative and may not obtain the desired result, which is the total regression of the lesion.